Pengembangan Informasi Layanan Kantor Urusan Agama Kecamatan Purwakarta melalui Instagram di Masa Pandemi - Fadillah, Rizal; Alna, Safura Amina; Herani, Shaviera Denti; Pratiwi, Inne Marthyane (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2022)
The conventional way of people receiving some information towards Purwakarta Religious Affairs Office's services might came up for the revitalisation still hasn't really come yet. For the local's scale of information spread still haven't come specific and lean on the centre of certain Religious Affair's division related. Looking around how people were asking for some digital informations related to Purwakarta Religious Affair's Office's services, and sometimes resulting lack of documents when they faced the administration staffs, the researches found out some potentials in the institution to be developed. This form of dedication as part of researcher's program would help to develop and provide some informations based in digital to get the Purwakarta Religious Affairs Office having higher chances to keep in touch closer with the people through easily accessible application for everyone. The following journey would be divided into 4 (four) stages; social reflection, plannings, excecuting, and monitoring plus evaluation. Objecting the Purwakarta Religious Affrais Office as the main aim of the programs, as it's part of Purwakarta Religious Affairs. The researchers also came up with some technical managements towards Purwakarta Religious Affrais Office's services in order to provide easier accessible informations through Instagram for the people. At the end of the day, the whole journey and its result produced great feedback from the Purwakarta Religious Affrais Office party, and also people around. For everyday from now on, the Purwakarta Religious Affrais Office's Intagram account always earn some new followers, and this brought people to the state of not having to go to the office to get the answer of their question towards the services of Purwakarta Religious Affrais Office